187k views
4 votes
Replace the values of mand n to show the solutions of this equation.X^2+ 6x – 5 = 0

Replace the values of mand n to show the solutions of this equation.X^2+ 6x – 5 = 0-example-1

1 Answer

3 votes

Given the quadratic equation below


x^2+6x-5=0

Using the method of completing the square we have that:


\begin{gathered} (x^2+6x)-5=0 \\ (x+3)^2-9-5=0 \\ (x+3)^2-14=0 \end{gathered}
\begin{gathered} (x+3)^2=14 \\ (x+3)=\pm\sqrt[]{14} \\ x=-3\pm\sqrt[]{14} \end{gathered}

Hence, from the above solution, the value of m is -3 and n is √14

User Mindan
by
5.9k points